Language Self-Assessment: The Comparison of Learning Difficulty and Readiness of Non-Language Department Students - Istianah, Tia Nur (research, training and philanthropy institution Natural Aceh, 2025)
Self-assessment in language learning is important to understanding students' needs and challenges in mastering Arabic and English skills, especially for those outside the language department. Therefore, this study aims to explore the differences in the level of language learning difficulty and the readiness of students from non-language majors to learn Arabic and English. This study uses a quantitative descriptive approach with a survey method, involving 109 students from three Islamic universities in the Cirebon area as respondents. Data was collected through a questionnaire consisting of two main components: the language learning difficulty scale and the learning readiness scale. Data analysis was carried out to compare the difficulty level felt with the student's readiness to learn English. The results showed that both variables had the same response in terms of difficulty and readiness to learn. The classification of difficulty in Arabic and English is the same, namely at a moderate level with a percentage of 64% and 51%, and the dominant indicator that is considered difficult for students to master is the fluency indicator. In addition, the comparison of learning readiness in Arabic and English did not differ significantly. The motivation indicators of both languages have the same percentage of 35%. Thus, the motivation of non-language students to learn Arabic and English is higher than the other two indicators.